2016
DOI: 10.1118/1.4939809
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal ablation of deep brain targets: A simulation study on a large animal model

Abstract: Purpose: Thermal ablation with transcranial MRI-guided focused ultrasound (FUS) is currently limited to central brain targets because of heating and other beam effects caused by the presence of the skull. Recently, it was shown that it is possible to ablate tissues without depositing thermal energy by driving intravenously administered microbubbles to inertial cavitation using low-duty-cycle burst sonications. A recent study demonstrated that this ablation method could ablate tissue volumes near the skull base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…As such, computational models that take into account individual skull morphology are warranted for accurate beam location and intensity. Detailed computational models of the skull are used in applications including aberration correction in high intensity focused ultrasound for thermal ablation (Marquet et al, ) and nonthermal ablation with microbubble enhanced focused ultrasound (Top, White, & McDannold, ). We were not able to acquire CT scans of the participants in this study and given the initial model shown here (despite a good conservation of beam geometry) it is recommended for future subcortical single‐element transcranial ultrasound studies that CT scans of individuals are acquired and detailed computational models run to ensure accurate target localization and transducer placement (Mueller et al ).…”
Section: Limitations and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, computational models that take into account individual skull morphology are warranted for accurate beam location and intensity. Detailed computational models of the skull are used in applications including aberration correction in high intensity focused ultrasound for thermal ablation (Marquet et al, ) and nonthermal ablation with microbubble enhanced focused ultrasound (Top, White, & McDannold, ). We were not able to acquire CT scans of the participants in this study and given the initial model shown here (despite a good conservation of beam geometry) it is recommended for future subcortical single‐element transcranial ultrasound studies that CT scans of individuals are acquired and detailed computational models run to ensure accurate target localization and transducer placement (Mueller et al ).…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…As such, computational models that take into account individual skull morphology are warranted for accurate beam location and intensity. Detailed computational models of the skull are used in applications including aberration correction in high intensity focused ultrasound for thermal ablation (Marquet et al, 2009) and nonthermal ablation with microbubble enhanced focused ultrasound (Top, White, & McDannold, 2016).…”
Section: I M I Ta Ti Ons An D Con S I De R At I Onsmentioning
confidence: 99%
“…Simulations were then carried out using software and services provided by the Minnesota Supercomputing Institute at the University of Minnesota. While these modeling methods may introduce uncertainties in results, such methods have been used successfully for aberration correction and forward problem simulations in previous literature [12,13,26,27].…”
Section: Computer Simulationsmentioning
confidence: 99%
“…It is the focus of this work to develop a model of transcranial focused ultrasound using detailed representations of the skull while regarding all other tissues as water, as the modeling of soft tissues has already been shown to have negligible effects [11]. Detailed computational models of the skull have been used previously in applications including aberration correction in high intensity focused ultrasound for thermal ablation [12] and non-thermal ablation with microbubble enhanced focused ultrasound [13]. In the present study, we developed computational models of the skull based on medical images to evaluate simulation methods for tFUS for noninvasive neuromodulation and to explore the differences in intracranial pressure maps between individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It can be noted that we haven’t considered methods for drastically lowering the frequency (220 kHz) to open the blood–brain barrier (BBB) and improve drug delivery [127130], with the use of microbubbles [131, 132], nanoparticles [133135], or contrast media [136]. Such a strategy is highly problematic [137, 138]. …”
Section: Discussionmentioning
confidence: 99%